Evaluation of the Effects of Bureaucracy on Public Expenditure Together with Rent Seeking Activity - İbrahim Keklik; Abdullah Barış (Maliye Çalışmaları Dergisi)
The duties undertaken by the state to meet social needs and to have an impact on social and economic life cause public expenditure to be made and increased on a regular basis. This increase in public expenditure has a positive effect on economic growth. One of the factors that has an impact on the planning and implementation of public expenditure is the bureaucracy. Bureaucrats may want to increase the sizeof their offices in order to increase their power, prestige and monetary authority, while adopting the aim of contributing to economic growth in the planning and implementation process of public expenditure. The increase in the size of officesallows the number of personnel to rise and this in turn has an effect on the service production capacity of the bureau causing potential changes in the hierarchical structure. The fact that bureaucrats are not an organic unit, but people who can make choices and have a set of attitudes and behavioral models, reveals that the decisions taken on public expenditure are taken in line with individual preferences. This situation results in a waste of resources in the economy through rent-seeking, and also negatively affects economic growth by making public expenditure inefficient. In this study, the effects of bureaucracy on public expenditure and bureaucratic behavior models affecting public expenditure are evaluated within the framework of rent-seeking activity.